2018
DOI: 10.1002/adfm.201806786
|View full text |Cite
|
Sign up to set email alerts
|

Laser Direct Writing of Ultrahigh Sensitive SiC‐Based Strain Sensor Arrays on Elastomer toward Electronic Skins

Abstract: Electronic skins (e-skins) have been widely investigated as important platforms for healthcare monitoring, human/machine interfaces, and soft robots. However, mask-free formation of patterned active materials on elastomer substrates without involving high-cost and complicate processes is still a grand challenge in developing e-skins. Here, SiC-based strain sensor arrays are fabricated on elastomer for e-skins by a laser direct writing (LDW) technique, which is mask-free, highly efficient, and scalable. The dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
134
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 63 publications
2
134
0
Order By: Relevance
“…Laser direct writing (LDW) has been recently introduced as an effective and scalable process for the manufacturing of wearable sensors. [154][155][156][157][158] For instance, LDW was used to develop stretchable strain sensor arrays by turning Ecoflex elastomer into silicon carbide conductive patterns through the localized laser irradiation. [158] Apart from the polymeric supporting materials, natural fibers, yarns, and fabrics have been activated by conductive materials through techniques such as carbonization process, dip-coating, bar coating, ultrasonication, and vacuum filtration.…”
Section: Fabrication Of Wearable Strain Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser direct writing (LDW) has been recently introduced as an effective and scalable process for the manufacturing of wearable sensors. [154][155][156][157][158] For instance, LDW was used to develop stretchable strain sensor arrays by turning Ecoflex elastomer into silicon carbide conductive patterns through the localized laser irradiation. [158] Apart from the polymeric supporting materials, natural fibers, yarns, and fabrics have been activated by conductive materials through techniques such as carbonization process, dip-coating, bar coating, ultrasonication, and vacuum filtration.…”
Section: Fabrication Of Wearable Strain Sensorsmentioning
confidence: 99%
“…[154][155][156][157][158] For instance, LDW was used to develop stretchable strain sensor arrays by turning Ecoflex elastomer into silicon carbide conductive patterns through the localized laser irradiation. [158] Apart from the polymeric supporting materials, natural fibers, yarns, and fabrics have been activated by conductive materials through techniques such as carbonization process, dip-coating, bar coating, ultrasonication, and vacuum filtration. [23,[143][144][145][146][147][148][149][150]152,[159][160][161][162][163] Carbonization is a well-established process where carbonaceous substances such as natural fibers are broken down into elemental carbon and chemical compounds by heating ( Figure 4a).…”
Section: Fabrication Of Wearable Strain Sensorsmentioning
confidence: 99%
“…During the past decade, flexible electronic devices have earned great achievements and attracted much interests, [1][2][3][4][5][6][7] especially the stretching sensor which has been greatly developed in wearable electronics devices, [8][9][10][11][12][13][14] flexible luminescence devices [15][16][17][18] and soft robotics. [19][20][21][22][23][24][25] Among different kinds of stretching sensor, ionic conductive hydrogel stretching sensor is considered to be the best materials for the human body motion sensor, due to the good electrochemical performance [26][27][28][29][30][31][32][33][34] and controllable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The product formed by modication of polymers is also not limited to graphitic carbon. There have been reports regarding the fabrication of advanced ceramic materials, such as titanium carbonitride (Ti(C,N)), 11 silicon carbonitride (Si(C,N)), 12,13 and silicon carbide (SiC), 14,15 from organometallic polymers. For example, Jakubenas et al reported the modication of polycarbosilane (PCS), an organosilane polymer, into crystalline 3C-SiC (b-SiC) using a $10.6 mm continuous wave (CW) CO 2 laser.…”
Section: Introductionmentioning
confidence: 99%